Urban rural inequities in breastfeeding practices in low- and middle-income countries: A Scoping Review - Herlianty Herlianty; Jusrawati Jusrawati; Evi Sri Dahrianti; Brenda Mpazo (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Breastfeeding is a critical intervention for reducing infant morbidity and mortality and improving maternal health outcomes. Despite global recommendations supporting early initiation and exclusive breastfeeding, substantial disparities persist across low- and middle-income countries (LMICs), particularly between urban and rural populations. Urban–rural inequities reflect complex structural, socioeconomic, and cultural determinants that influence breastfeeding practices beyond maternal knowledge. This scoping review aimed to systematically map evidence on urban–rural differences in breastfeeding practices in LMICs and to identify key determinants contributing to these disparities. Research Methodology: A scoping review was conducted following Arksey and O’Malley’s framework and the Joanna Briggs Institute guidelines, with reporting aligned to PRISMA-ScR. Four databases (PubMed, Scopus, CINAHL, and ProQuest) were searched for studies published between 2015 and 2025. Eligible studies were original research conducted in LMICs that compared breastfeeding outcomes across urban and rural settings. Data were extracted, charted, and synthesised narratively. Results: Seven cross-sectional studies from Ethiopia, Tanzania, Lao PDR, Indonesia, Nigeria, Niger, and Sierra Leone were included. Most studies demonstrated a higher prevalence of early initiation and exclusive breastfeeding in rural areas despite limited health service access. Urban residence, increasing infant age, caesarean delivery, maternal employment, and exposure to formula marketing were consistently associated with suboptimal breastfeeding. Conclusion: Urban–rural disparities in LMICs are driven by structural and contextual inequities rather than maternal intention alone. Policies should prioritise breastfeeding-friendly workplace regulations, enforcement of the International Code of Marketing of Breast-milk Substitutes, and culturally responsive maternal support systems.